2008
DOI: 10.1073/pnas.0802702105
|View full text |Cite
|
Sign up to set email alerts
|

Death receptor 5 mediated-apoptosis contributes to cholestatic liver disease

Abstract: Chronic cholestasis often results in premature death from liver failure with fibrosis; however, the molecular mechanisms contributing to biliary cirrhosis are not demonstrated. In this article, we show that the death signal mediated by TNF-related apoptosisinducing ligand (TRAIL) receptor 2/death receptor 5 (DR5) may be a key regulator of cholestatic liver injury. Agonistic anti-DR5 monoclonal antibody treatment triggered cholangiocyte apoptosis, and subsequently induced cholangitis and cholestatic liver injur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
130
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 129 publications
(137 citation statements)
references
References 48 publications
5
130
0
2
Order By: Relevance
“…For instance, FcγRIIB expression in B cells plays a significant role in driving the immunostimulatory activity of agonistic αCD40 antibodies, likely because B cells are the most abundant FcγRIIB-expressing cells in lymphoid tissue, where CD40 on antigen-presenting cells is targeted. In contrast, FcγRIIB expression in CD11c + and LysM + cells, not B cells, is required for the hepatotoxic effect of agonistic αDR5 antibodies, which could be explained by the fact that residential macrophages and dendritic cells are rich and B cells are rare in liver, where DR5 on cholangiocytes is targeted (24,25). Similarly, most immune cells infiltrated into tumor tissue are CD11b + myeloid cells (10), which may explain a dominant role of FcγRIIB expression in these cells in driving the antitumor activity of agonistic αDR5 antibodies.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…For instance, FcγRIIB expression in B cells plays a significant role in driving the immunostimulatory activity of agonistic αCD40 antibodies, likely because B cells are the most abundant FcγRIIB-expressing cells in lymphoid tissue, where CD40 on antigen-presenting cells is targeted. In contrast, FcγRIIB expression in CD11c + and LysM + cells, not B cells, is required for the hepatotoxic effect of agonistic αDR5 antibodies, which could be explained by the fact that residential macrophages and dendritic cells are rich and B cells are rare in liver, where DR5 on cholangiocytes is targeted (24,25). Similarly, most immune cells infiltrated into tumor tissue are CD11b + myeloid cells (10), which may explain a dominant role of FcγRIIB expression in these cells in driving the antitumor activity of agonistic αDR5 antibodies.…”
Section: Discussionmentioning
confidence: 88%
“…In addition, different agonistic anti-TNFR antibodies require different FcγRIIB expression levels, which may be related to several factors, including the efficiency of the involved antibody being cross-linked by FcγRIIB, the expression levels of the targeted TNFR, and the amount of cross-linking required to activate the targeted TNFR in the targeted cells. Both agonistic αFas and αDR5 antibodies mediate their hepatotoxic effects by triggering a Fas-associated protein with death domain-dependent apoptotic signaling pathway, but liver cells appear to be more sensitive to apoptosis mediated by Fas than by DR5, as hepatocytes are more sensitive to FasL than TRAIL even though both Fas and DR5 are expressed (24). Therefore, it is reasonable to hypothesize that, to be activated in liver cells, Fas requires less cross-linking and thus lower FcγRIIB expression than DR5.…”
Section: Discussionmentioning
confidence: 99%
“…A better understanding of the failure mechanism might improve the development of mAb-based cancer therapies. Although we did not observe any toxicity of the single or combination mAbs in our study and MD5-1 can be administered safely to BALB/c mice at very high doses (26,32), cholangiocyte toxicity and bile duct occlusion is observed in C57BL/6 mice treated with high doses of MD5-1, and hepatotoxicity with increased serum alanine aminotransferase, aspartate aminotransferase, and bilirubin was reported in a few patients when treated with higher doses (20 mg/kg) of lexatumumab (human anti-human DR5) (33). It is too early to know whether hepato-or bile duct toxicity might limit anti-DR5-based therapeutic approaches in humans, but care needs to be taken when progressing to combination therapies in humans where new sensitivities to the TRAIL-DR5 pathway may manifest.…”
Section: Discussionmentioning
confidence: 95%
“…We investigated the accelerated mortality of Fcer1g −/− mice treated with MD5-1 to determine the cause of this toxicity. Previous studies demonstrated that MD5-1 induced hepatotoxicity in a strain-dependent manner, resulting in cholestatic liver injury in B6 mice, but not in BALB/c mice (34). In susceptible strains like B6, MD5-1 treatment triggers apoptosis in cholangiocytes and causes cholestatic liver disease.…”
mentioning
confidence: 99%